Henderson's dictionary of biology (Pearson / Prentice Hall, 2005)
The thirteenth EDITION of this classic dictionary has been updated in response to changes in the core life-sciences fields, and now includes new terms from bioinformatics, genomics, and proteomics. Key Features middot; over 22,000 entries middot; clear definitions and additional explanations middot; covers a wide range of topics middot; includes new terms since the last EDITION, e.g. chameleon sequence, metabolomics, protein chip, boundary elements, lipid raft, LUCA, RNA interference, ontology middot; includes simplified, up-to-date classification tables for the kingdoms of living organisms HENDerson's Dictionary of Biology continues to provide an essential reference for students of any of the biological sciences and for teachers and researchers. Eleanor Lawrence is a freelance science writer and editor, and co-AUTHOR of Longman Dictionary of Environmental Science.